Translation in the Tourism Industry: Terminological Challenges and Solutions (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The translation of tourism-related content involves specific terminological challenges due to the sector’s dynamic, culture-sensitive nature. This article explores key terminological issues faced by translators in the tourism industry and examines strategies for overcoming them, emphasizing the importance of context in the translation process. The study employs literature analysis and comparative methodology to highlight effective translation practices.